Home Telemedicine (CoYoT1 Clinic): A Novel Approach to Improve Psychosocial Outcomes in Young Adults With Diabetes. Issue 4 (August 2019) - Bakhach, Marwan; Reid, Mark W.; Pyatak, Elizabeth A.; Berget, Cari; Cain, Cindy; Thomas, John "Fred"; Klingensmith, Georgeanna J.; Raymond, Jennifer K.
Purpose: To assess the impact of a home telemedicine clinic model (CoYoT1 Clinic) on psychosocial and behavioral outcomes designed for young adults (YAs) with type 1 diabetes (T1D). Methods: YAs self-selected to participate in the CoYoT1 Clinic or serve as a usual care control. CoYoT1 Clinic visits consisted of an individual appointment with a provider and a group appointment with other YAs with T1D using home telemedicine. Psychosocial and behavioral functioning was assessed by 4 measures: Diabetes Distress Scale, Self-Efficacy for Diabetes Scale, Self-Management of Type 1 Diabetes in Adolescence Scale, and Center for Epidemiologic Studies Depression Scale. Results: Forty-two patients participated in the CoYoT1 Clinic and 39 patients served as controls. CoYoT1 participants reported lower levels of distress ( P = .03), increased diabetes self-efficacy ( P = .01), and improved ability to communicate with others about diabetes ( P = .04) over the study period compared to controls. YA males in the control group reported increases in depressive symptoms ( P = .03) during the study period, but CoYoT1 participants showed no changes. Conclusion: Group home telemedicine for YAs with T1D positively affects diabetes distress, self-efficacy, and diabetes-specific communication. These positive findings have the potential to also affect the YAs' long-term diabetes outcomes. Further investigation of the model is needed.